The Goblin Spiders of the Genus Opopaea (Araneae, Oonopidae) in Hainan Island, China - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2010)
Seven species of Opopaea are recognized from Hainan Island, China. Four species are found to be new to science: Opopaea diaoluoshan sp. nov. (male/female), Opopaea furcula sp. nov. (male/female), Opopaea sanya sp. nov. (male) and Opopaea vitrispina sp. nov. (male/female). One species, Opopaea sauteri Brignoli, 1974 is firstly recorded from this area. All of them, including the two previously known species, Opopaea cornuta Yin & Wang, 1984 and Opopaea gibbifera Tong & Li, 2008, are diagnosed and illustrated. A key to all the seven species of Hainan Island is provided.